The Improvement of Indonesian Language Learning Outcomes in Poetry Writing Materials Through the Real Experience Method for Year VIII-A Students of Madrasah Tsanawiyah Negeri 3 West Aceh in the 2021/2022 Academic Year - Hardianto, Suji (LUMBUNG AKSARA, 2022)
This study aims to determine "The Improvement of Indonesian Language Learning Outcomes in Poetry Writing Materials Through the Real Experience Method for Year VIII-A Students of Madrasah Tsanawiyah Negeri 3 West Aceh in the 2021/2022 Academic Year". This study used Classroom Action Research (CAR) with the methods of observation, data collection, tests, documentation and data analysis. This study used two cycles to determine the improvement of Indonesian language learning outcomes for writing poetry in Year VIII-A class of MTsN 3 West Aceh in the 2021-2022 academic year. The results of this study indicated that the Real Experience Method can improve students’ learning outcomes in class VIII-A Madrasah Tsanawiyah Negeri 3 West Aceh. As for the results, it can be seen from the learning outcomes in the pre-cycle, the first and second cycles. The percentage of the students who reached the learning target in the first cycle was 65% and the second cycle was 85% that was increased by 20%. So with these results, the learning target of the students was successfully achieved.